Performance of the digital trail making test in older adults with white matter lesions - Shan, Xinjun; Tian, Le; Zhao, Hongyi; Zhao, Xiuli; Wei, Fangyuan (Frontiers in Human Neuroscience, 2025)
BackgroundStudies have reported that digital assessment technology coupled with the traditional Trail Making Test (TMT) can capture additional information about a new cognitive domain.ObjectivesThe goal of the current study is to demonstrate the performance of the digital Trail Making Test (dTMT) in older people with white matter lesions (WML).MethodsIn this single-center, observational study, 18 elderly patients with WML admitted to our hospital from June 2021 to June 2022 served as the WML group, and 18 participants matched for age, gender, and educational level who were undergoing physical examination in our hospital during the same period served as the control group. The participants completed the dTMT Part A (dTMTA) and dTMT Part B (dTMTB) to obtain the outcomes, such as dTMT completion time, number of errors, time inside each circle, total pathway deviation of each step, and velocity of drawing of each step. The severity of WML was scored using the Fazekas scale. Multiple neuropsychological assessments were carried out to assess cognitive function. The Purdue Pegboard Test (PPT) was used to display the unimanual dexterity (dominant hand task) and fine motor control (assembly task). The relationships between dTMT variables and cognition and motion in elderly patients with WML were analyzed using linear regression analysis.ResultsThe WML group required significantly more time to complete the dTMTA (19.78 ± 1.92 s vs. 18.17 ± 1.72 s, p = 0.012) and dTMTB (38.83 ± 4.33 vs. 34.00 ± 2.99, p < 0.001). For dTMTA, larger pathway deviation (43.76 ± 4.50 vs. 39.81 ± 4.66, p = 0.014) and lower velocity (17.05 ± 4.72 vs. 20.50 ± 4.00, p = 0.024) were found in the WML group. For dTMTB, longer time in the circle (30.02 ± 7.19 vs. 16.22 ± 4.70, p < 0.001), larger pathway deviation (47.00 ± 4.40 vs. 41.96 ± 6.44, p = 0.010), and lower velocity (11.48 ± 2.75 vs. 14.18 ± 3.86, p = 0.021) were exhibited in aged individuals with WML. Linear regression analysis showed that the time spent inside each circle showed a positive correlation with the Mini-Mental State Evaluation (MMSE) (p = 0.015, standardized β = 0.454) and PPT unimanual task (p = 0.024, standardized β = 0.420) for dTMTA; and the total time to completion was negatively correlated with the PPT assembly task (p = 0.001, standardized β = −0.583).ConclusionOlder adults with WML showed abnormalities while solving the dTMT. dTMT might be a potential indicator for cognitive and fine motor deficits in patients with WML.